Electrochemical Fabrication of Graphite Oxide Nanosheets with Stable Photoluminescence and Their Photocatalytic Performance in Visible Light - Zhao, X.M.; Malik, M.J. (Asian Journal of Chemistry, 2013)
Graphite oxide nanosheets surface-passivated by ethylene glycol (GONs-EG) were synthesized by a green electrochemical method. GONs-EG exhibited blue luminescence and high up-conversion photoluminescence, also showed peroxidase mimetic function and visible-light-sensitive photocatalytic activity.